1999
DOI: 10.1063/1.477985
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative sticking of CH4 on Ru(0001)

Abstract: In this study the CH 4 dissociation probability on Ru͑0001͒ is found for various translational and vibrational energies. The absolute sticking values are determined from King and Wells experiments and carbon uptake curves. The carbon amount is determined from the recombination signal of carbon with oxygen obtained after the beam exposure when heating in an oxygen atmosphere. The measured sticking coefficient of CH 4 is strongly enhanced both by increasing the translational and the vibrational energy of the CH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…This has now been reported for a number of systems, CH 4 /Ni(111) [23,24], CH 4 /Ni(100) [25], CH 4 /Ru(0001) [26] and even for the "simple" N 2 /Ru(0001) [27,28] case. Several hypotheses have been proposed in order to explain the "surprising" results Θ vib (R) > 1: It has been suggested that if the asymptotic reactivity (i.e., the saturation value of the dissociation probability) increases for vibrationally excited molecules, then Eq.…”
Section: Introductionmentioning
confidence: 52%
“…This has now been reported for a number of systems, CH 4 /Ni(111) [23,24], CH 4 /Ni(100) [25], CH 4 /Ru(0001) [26] and even for the "simple" N 2 /Ru(0001) [27,28] case. Several hypotheses have been proposed in order to explain the "surprising" results Θ vib (R) > 1: It has been suggested that if the asymptotic reactivity (i.e., the saturation value of the dissociation probability) increases for vibrationally excited molecules, then Eq.…”
Section: Introductionmentioning
confidence: 52%
“…A number of molecular beam experiments in which the dissociation energy was measured as a function of translational energy have observed that vibrationally hot CH 4 dissociates more readily than cold CH 4 , with the energy in the internal vibrations being about as effective as the translational energy in inducing dissociation. [1][2][3][4][5][6][7] Two independent bulb gas experiment with laser excitation of the 3 asymmetrical stretch and 2 4 umbrella modes on the Rh͑111͒ surface, 8 and laser excitation of the 3 and 2 3 modes on thin films of rhodium 9 did not reveal any noticeable enhancement in the reactivity of CH 4 . A recent molecular beam experiment with laser excitation of the 3 mode did succeed in measuring a strong enhancement of the dissociation on a Ni͑100͒ surface.…”
mentioning
confidence: 93%
“…Some experiments have also observed that vibrationally hot CH 4 dissociates more readily than cold CH 4 , with the energy in the internal vibrations being about as effective as the translational energy in inducing dissociation. [2][3][4][7][8][9][10]13 A molecular beam experiment with laser excitation of the 3 mode did succeed in measuring a strong enhancement of the dissociation on a Ni͑100͒ surface. However, this enhancement was still much too low to account for the vibrational activation observed in previous studies and indicated that other vibrationally excited modes contribute significantly to the reactivity of thermal samples.…”
Section: Introductionmentioning
confidence: 99%